Placental Development and Pregnancy-Associated Diseases - Xin Yu; Hongyu Wu; Yun Yang; Feiyang Wang; Yan-Ling Wang; Xuan Shao; Dandan Shi (Wolters Kluwer Health, 2022)
Abstract. Serving as the interface between the fetal and maternal environments during gestation, the placenta plays critical roles in the protection of the developing fetus and the maintenance of maternal health. The placenta is primarily derived from the embryonic trophectoderm which differentiates into various subtypes of trophoblast cells through villous and extravillous pathways. The interactions among trophoblasts and multiple decidual cells and immune cells at the maternal-fetal interface fundamentally form the functional units of the placenta, which are responsible for blood perfusion and maternal-fetal material exchange, immune tolerance, and the regulation of pregnancy adaptation. Defects in placental development and functional maintenance are in tight association with adverse pregnancy outcomes such as preeclampsia. In this article, we review recent advances on human trophoblast cell differentiation and the construction of placental functional units and discuss the placental and maternal factors that may contribute to the occurrence of preeclampsia.